A cohort study investigating the effects of first stage of the English tobacco point-of-sale display ban on awareness, susceptibility and smoking uptake among adolescents - Bogdanovica, Ilze; McNeill, Ann; Britton, John (BMJ Publishing Group Ltd, 2017)
Objective: A prospective evaluation of the effect of 2012 point-of-sale (PoS) display ban in supermarkets in England on perceived exposure to PoS displays, and on changes in susceptibility and smoking uptake among young people. Design: Cohort study Settings: Seven schools in Nottinghamshire, England Participants: 1,035 11-16 year-old schoolchildren Primary and secondary outcome measures: Changes in reported exposure to PoS displays before and after prohibition, and the association between exposure to and awareness of PoS displays and change in susceptibility to smoking and smoking status between 2011 and 2012 (before the ban) and 2012 and 2013 (after the ban). Results: The proportion of children noticing tobacco PoS displays in supermarkets most or every time they visited a shop changed little between 2011 and 2012 (59.6% (95% confidence interval 56.6%- 62.6%) and 58.8% (95% confidence interval 55.8%- 61.8%), respectively); but decreased by about 13 percentage points to 45.7% (95% confidence interval 42.7%-48.7%) in 2013, after the ban. However, after adjusting for confounders, implementation of the first stage of the PoS ban in 2012 did not result in significant changes in the relation between susceptibility to smoking and smoking status and exposure to and awareness of PoS displays. Conclusions: Prohibition of PoS in large supermarkets resulted in a decline in the proportion of young people noticing PoS displays in large shops, but little or no change in smoking uptake or susceptibility. It remains to be seen whether extension of the PoS ban to all shops in 2015 has a more marked effect.